Impacts of Artificial Intelligence Integration on Teaching Practices and Student Engagement in Digitally Transformed Educational Settings - Heri Nurdiyanto; Leonel Hernandes; Aktansi Kindiasari (Jurnal Pendidikan Teknologi dan Kejuruan, 2025)
This study explores how the integration of artificial intelligence (AI) into digitally transformed educational settings reshapes everyday teaching practices and influences student engagement in real learning contexts. Rather than treating AI as a standalone technological upgrade, the study situates its use within the broader transformation of digital learning environments, where platforms, automated tools, and data-driven systems increasingly mediate classroom interactions. The findings show that AI integration gradually shifts the role of teachers from primarily delivering content toward designing learning experiences, guiding students’ learning processes, and responding to more diverse patterns of participation. In practice, AI-supported tools help streamline routine instructional tasks, open space for more personalized interaction, and provide timely support to students with different learning needs. At the same time, the results indicate that student engagement does not automatically improve simply because AI is introduced. Engagement grows when AI tools are meaningfully aligned with pedagogical goals, integrated into everyday learning activities, and supported by teachers’ readiness to adapt their instructional strategies. The study also highlights emerging tensions, including uneven levels of student participation, varying degrees of teacher confidence in using AI-based systems, and concerns about over-reliance on automated support. Overall, the findings suggest that the impact of AI in digitally transformed educational settings is shaped less by the technology itself than by how it is embedded in teaching practices and learning cultures, pointing to the importance of thoughtful integration in sustaining meaningful student engagement.